Power-load relationship of bench press, ballistic bench press, and prone bench pull in international medal-winning canoeists and kayakers - Crisafulli, O.; Fortunati, M.; Gemelli, T.; Febbi, M.; Drid, P.; Ramat, S.; D`Antona, G. (Sports, 2025)
Paddler athletes use resistance training (RT) to optimize power output (PO) during competitions. Understanding the power-load relationship (P-Lr) is essential for effective RT prescription. Moreover, the push-to-pull ratio (PU/PR)—the one-repetition maximum (1RM) of a pulling exercise divided by the one of a pushing exercise—has been suggested as a metric associated with sprint kayak performance. This study aimed to describe P-Lr in three guided exercises (bench press (BP), ballistic bench press (BBP), and prone bench pull (PBP)), along with PU/PR in international-level canoeing and kayaking athletes. Nine male athletes (21.0 ± 1.5 years) were monitored during two sessions of an incremental testing protocol. Load ranged from 30 to 100 kg in BP, 30 to 95 kg in PBP, and 20 to 60 kg in BBP. Instantaneous displacement was measured using a linear position transducer, and PO was computed for each repetition and exercise. PU/PR was calculated upon PBP and BP. A two-way repeated-measures ANOVA was used to explore differences among exercises and relative load from 20% to 90% 1RM. PBP displayed a higher PO between 40% and 90% 1RM compared to BP and BBP), while no statistical difference was found between BP and BBP at any relative load. Additionally, mean PU/PR resulted 0.96. This study provides preliminary values regarding P-Lr and PU/PR in elite paddlers, which may assist in designing training programs for those targeting major competitions.